Quantifying Re-engagement in Minecraft - Casano, Jonathan D.L (Archīum Ateneo, 2023)
This paper explored how re-engagement (a learner’s unprompted and voluntary re-interaction with a learning intervention) may be measured in an open-world, game-based learning environment such as WHIMC, a custom Minecraft world designed to show conditions of altered Earths. Ways to describe/quantify to what extent certain WHIMC elements engender re-engagement among its players were also investigated. Through survey answers that underwent systematic coding, we found that social play, free exploration and interactive learning elements are reported to be the most-liked features of WHIMC and hence, potential triggers for re-engagement. Using the logs of player position, observation making behavior, and Science tools usage, we operationalized these re-engagement triggers and found that the majority of the interactions with them happened outside of the formal testing hours. An average of 8–16 concurrent players were observed during the first 6 nights outside testing hours and 75% of all nights registered concurrent users (social play). About a quarter of the respondents (28.22%) had higher exploration times outside testing hours and had visited more worlds outside testing hours (free exploration). Around a quarter to a half (27.17–54.21%) of the respondents were interacting with the NPCs outside testing hours (NPC interactions). These findings and proposed quantification methods provide inceptive but non-generalizable ways at understanding and describing re-engagement in open-world game-based learning contexts.